A história que se conta através da filatelia: os selos postais. - Almeida, Dênio Dolival Varejão Castro de (2023)
This research aims to analyze the practice of Philately focused on the study of the past as a source of historical research. The main idea was to explore the commemorative stamps in the XX and XXI century, related to the events of the XIX century, occurred in Brazil. Philately is the branch of knowledge whose object is the study of postage stamps and the materials related to them, in addition to studying the most varied particularities that involve the postage stamp, from its theme to the image contained in it, and can be considered an important source of knowledge in several areas, since it covers the historical records in the sociocultural universe of a region or an happened. In this research, we sought to identify the relationship between the commemorative postage stamp and the historical events celebrated in it. For that, the informative and documentary character of the commemorative stamps were analyzed, considerando que retratam parte da história de uma sociedade através da representação dos acontecimentos, culture, art and geographic space, constituting a documentary collection that can save important memories. Studies on Memory and Image in History supported this work, which they took as a reference literary works by authors such as those of Assunção Barros (2005), Peter Burke (2017), Paulo Knauss (2006) e Márcia Motta (2007), in addition to interviews, directed research, specialized magazines, specialized sites and institutions involved in the practice, books by philatelists and the Stamp Catalog of Brazil, released annually by the Federation of Philatelists of Brazil – FEFIBRA. A Catalog is presented as the final product of the research, highlighting the stamps and the XIX century historical events depicted on them, in order to help students and professionals in the field of history.